Profile of patients with intellectual disability visiting a tertiary care center in western India - Shah, Parag S.; Shukla, Srivani D.; Patel, Asha A.; Patel, Shivangi S. (International Journal of Research in Medical Sciences, 2017)
Background:Intellectual disability is commonly associated with variety of etio-pathological and co-morbid conditions influencing outcome of rehabilitative measures. Understanding of these factors helps in better management of disabled condition. Methods:A qualitative retrospective case record review, of patients with intellectual disability, visiting psychiatry department of a tertiary care hospital, within a period of one year, was conducted to assess their epidemiological and clinical profile. Results: Patients with Intellectual disability are brought to the hospital at all ages and commonly by their parents. Etiologically related various peri-natal factors (delayed birth cry and seizures being most common) as well as childhood medical conditions (epilepsy and recurrent respiratory/GI infections being most common) were commonly found in these patients. Milestones are delayed in almost 60-70% of cases whereas various physical and psychiatric conditions commonly co-existed with disability. Conclusion:Clinical profile of these patients demands a comprehensive evaluation and management apart from routine IQ assessment.